Stress relaxation behaviour and mechanism of heat treated inconel 718 in high temperature environments - Bapokutty, Omar; Sajuri, Zainuddin; Junaidi, Syarif (AMREC SIRIM Malaysia, 2013)
The stress relaxation behaviour of heat treated nickel-base superalloy Inconel 718 at high temperature was investigated. Solution treatment was applied on the as-received material at 980 oC for 1 hour before water quenching followed by double aging treatments at 720 oC for 8 hours and 621 oC for 8 hours, then cooled in air. The stress relaxation test was conducted at 1 % strain at different test temperatures of 550 oC, 650 oC and 750 oC. The tests were carried out for a total of 72 hours. The tests were interrupted at 3 hours and 48 hours to investigate the evolution of microstructure and changes in material properties by using Scanning Electron Microscope (SEM) and X-Ray Diffractometer (XRD). The results showed that thermal dependent stress increased with decreasing temperature. In contrast, stress relaxation rate increased with increasing temperature. Microstructure observation by SEM showed that recovery process occurred. This was further supported by the decrease in dislocation density with increase in time and temperature, which is in-line with the Vickers micro-hardness results.